Clinicopathological, Histopathological, and Immunohistochemical Analysis of Mandibular Fibrosarcoma in a DSH Cat: A Case Report - Mahmood Ahmadi‐hamedani; Hamid Reza Moslemi; Sahar Ghaffari Khaligh; Mehdi Sedghi; Kimia Sattari (Veterinary Medicine and Science)
ABSTRACT A 4‐year‐old white male DSH cat was presented to the Veterinary Hospital on 18 December 2023, with a history of lethargy, loss of appetite, and salivation. During the inspection of the oral cavity, unilateral swelling was observed on the ventral side of the jaw. Before any therapeutic intervention, a cell blood count (CBC) test and FNA cytology were conducted. A five‐day course of adjunctive treatment, including ceftriaxone (5.5 mg/kg via IV) and clindamycin (25 mg/kg via IV), was given due to a suspicion of infection. Pantoprazole, metoclopramide (administered at 1 mg/kg via IV and IM), and duphalyte 500 mL (10 mL/kg IV) were used concurrently to alleviate nausea and stimulate appetite. Following a lack of improvement, a radical excision procedure was performed on tooth number 304 after the 5‐day treatment to excise the mass for histopathology and immunohistochemical analysis. The observation of mitotic bodies, pleomorphism, necrosis, and haemorrhage were consistent with malignancy, and squamous cell carcinoma (SCC) was suspected. Immunohistochemical staining was positive for the vimentin marker, the S‐100 protein, and desmin. This report describes a rare case of oral fibrosarcoma in a DSH cat in Iran.